Quality of life measurement in cancer patients before and after chemotherapy with EORTC QLQ-C30 in RSUP Dr. Sardjito Yogyakarta - Perwitasari, Dyah Aryani (Indonesian Journal of Pharmacy, 2009)
The research about cancer patients’ quality of life on before and after therapy of high emetogenic cytotostatic in RSUP Dr Sardjito Yogyakarta by EORTC QLQ-C30 has been done.This research used cohort design with cancer patients who just the first time received cisplatin ≥ 50 mg/m2 and or its combination, and also got ondansetron-dexamethasone as anti-emetics. While the patients were given EORTC QLQ-C30 questionnaire before got cisplatin (before chemotherapy) and 5 days after got cisplatin (after chemotherapy). The difference of the quality of the life will be analysed with paired t-test with 95 % level of significancy. The correlation between the domains before and after chemotherapy was analysed by Pearson correlation test with the 95 % level of significancy.We got 38 patients during 2 months with the cancer diagnoses of cervix, nasopharyng, ovarium and lung. Generally, the quality of life was nonsignificantly decreasing, whereas not all the domains were decreasing. The physical, emotions, cognitive and social domains were non-significantly increasing. The decline in the quality of life was more influenced by the role domain of the patients, pain, the decline in appetite and the financial difficulty. The correlation of fatigue, constipation and the financial difficulty were strong between the domain in before and the chemotherapy after was received in the symptom (r ≈ 0.50).Key words : quality of life, cancer, EORTC QLQ-C30.